Evaluation of the immunogenic property of NT H. influenzae protein D with Neisseria meningitidis OMV in BALB/c - Behrouzi, Ava; Bouzari, Saeid; Siadat, Seyed Davar; Oloomi, Mana; Davari, Mehdi; Mazaheri, Hoora (The Journal of Infection in Developing Countries, 2016)
Introduction: Identifying ideal non typeable Haemophilus influenzae (NTHi) vaccine candidates has not been easy due to extensive sequence and antigenic variation among gene products interacting with the immune system. Protein D (PD) is a highly conserved 42 kDa surface lipoprotein available in all H. influenzae, including NTHi. Methodology: In this study, the gene encoding PD was cloned from H. influenzae and expressed in Escheriachia coli TOPO10 cell in pBAD vector. Arabinose was used to express recombinant protein. In order to purify the protein, Ni-NTA agarose was used to perform affinity chromatography. Purified PD and PD mixed with outer membrane vesicle (OMV) and alum adjuvant were used for subcutaneous immunization in BALB/c mice. After vaccination, IgG responses to PD-OMV, PD-alum, and PD alone were determined by enzyme-linked immunosorbent assay (ELISA). Results: The recombinant PD containing His6 residues showed a molecular weight of 42 kDa. Anti-PD IgG was detected after first immunization in all groups of mice compared to the negative control group, and it increased after first vaccination, but results showed that the addition of OMV to PD led to a remarkable increase in IgG responses. Conclusions: Our results suggest an important role for OMV as an adjuvant and show how it could potentially be used when conjugated to H. influenzae PD or other safe subunit vaccine candidates.